2018
DOI: 10.1590/1414-431x20187786
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the putative furin recognition site 742RNRR745 for antiangiogenic Sema3C activity in vitro

Abstract: Angiogenesis is one of the key processes in the growth and development of tumors. Class-3 semaphorins (Sema3) are characterized as axon guidance factors involved in tumor angiogenesis by interacting with the vascular endothelial growth factor signaling pathway. Sema3 proteins convey their regulatory signals by binding to neuropilins and plexins receptors, which are located on the effector cell. These processes are regulated by furin endoproteinases that cleave RXRR motifs within the Sema, plexin-semaphorins-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, there are exceptions as in the case of sema3E in which the cleaved product retains full activity [12,13,14]. In contrast, cleavage in the basic domain potentiated the activity of sema3A [10] and there are reports suggesting that cleavage at this site may be essential for the anti-angiogenic activities of sema3F and sema3C [15,16].…”
Section: The Class-3 Semaphorin Subfamilymentioning
confidence: 99%
“…However, there are exceptions as in the case of sema3E in which the cleaved product retains full activity [12,13,14]. In contrast, cleavage in the basic domain potentiated the activity of sema3A [10] and there are reports suggesting that cleavage at this site may be essential for the anti-angiogenic activities of sema3F and sema3C [15,16].…”
Section: The Class-3 Semaphorin Subfamilymentioning
confidence: 99%
“…Our results demonstrated that SEMA3C reduced angiogenesis in HRGECs by inhibiting migration. The negative effect of SEMA3C depended on its C-terminal portion since the basic domain is involved in its binding to NRPs [12,[16][17][18].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It has been known that cleavage of SEMA3C at 549 RSRR 552 by FPPCs diminishes SEMA3C function [12,[16][17][18], and we generated SEMA3C mutants, FR and truncated (p65) forms. Generation and validation of these mutant constructs are detailed in online suppl.…”
Section: Sema3c Reduced Angiogenesis Of Hrgecs By Inhibiting Migrationmentioning
confidence: 99%
“…This nuance indicates that under any given biological context not only are levels of SEMA3C relevant but so too are the levels and repertoire of enzymes that modify SEMA3C. To this end, we and others have developed cleavage-resistant forms of SEMA3C in an effort to compensate for SEMA3C truncations [16,39,139,140,141]; however, a systematic analysis correlating various forms of SEMA3C and their activities would be informative. In two recent studies, Mumblat et al [139] and Yang et al [140] showed that a truncated version of SEMA3C harboring a deletion of the c-terminal 13 amino acids or wild type cleavable SEMA3C, respectively, inhibited angiogenesis but did not affect cell growth.…”
Section: Perspectivementioning
confidence: 99%